The correct use of the ART approach - Frencken, Jo E. (2010)
Confusion exists amongst dentists and scientists about the correct use of the caries management approach termed atraumatic restorative treatment (ART). Inconsistent use of the original definition of ART and suggested modifications (mART) have led to misunderstanding, misconception and miscommunication in the dental literature over the last decade. The aim of this paper is to contribute to a uniform understanding and use of the term ART. Adherence to its original description is suggested and two major aspects were addressed: the use of hand instruments only and the use of adhesive materials and systems.